2015
DOI: 10.1109/taes.2014.120103
|View full text |Cite
|
Sign up to set email alerts
|

Biased PNG for target observability enhancement against nonmaneuvering targets

Abstract: This paper proposes a biased proportional navigation guidance (BPNG) law providing enhanced target observability for passive homing missile systems against a nonmaneuvering target. After examining the line-of-sight (LOS) rate equation, which is an important parameter of target observability and which reveals that the LOS rate is proportional to the rate of cross-range deviation, a bias term of BPNG is formulated using the rate of cross-range deviation to generate an additional LOS rate. The closed-form traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Due to the removal of mechanically stable platform, the measurement of strapdown seeker is coupled with body attitude motion, such that the line-of-sight (LOS) angle and/or its angular rate required to compute guidance command cannot be measured. Only a body-referenced LOS angle, called body-LOS (BLOS) angle, can be fed to the guidance system [2], [3]. Moreover, compared to the gimbaled seeker, the strapdown seeker has a relatively narrower total field-of-view (FOV), which would be far more likely to violate the lock-on condition and cause mission failure [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the removal of mechanically stable platform, the measurement of strapdown seeker is coupled with body attitude motion, such that the line-of-sight (LOS) angle and/or its angular rate required to compute guidance command cannot be measured. Only a body-referenced LOS angle, called body-LOS (BLOS) angle, can be fed to the guidance system [2], [3]. Moreover, compared to the gimbaled seeker, the strapdown seeker has a relatively narrower total field-of-view (FOV), which would be far more likely to violate the lock-on condition and cause mission failure [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, severe measurement errors introduced by the strapdown seeker make it difficult to achieve an accurate estimation. Moreover, with few exceptions of [2], [32], [33], preexisting laws pay little attention to maintaining sufficient observability during the homing phase, with result that the filter/estimator cannot work properly [2].…”
Section: Introductionmentioning
confidence: 99%
“…2527 In 2012–2015, several new ideas about impact-angle-control by using combined guidance laws of PN and biased PN were proposed by Erer et al. 2832 In addition, some new guidance strategies of impact-angle-control were also reported in literatures 3336 in the case of without LOS angle rate information or with the limit of seeker’s field-of-view.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sliding-mode guidance laws with terminal angle constraint have been proposed by Kumar et al; [20][21][22][23] a biased PN guidance law for impact with angular constraint has been derived by Kim et al 24 and a two-stage PN guidance law related to the initial values has been reported in literatures. [25][26][27] In 2012-2015, several new ideas about impact-angle-control by using combined guidance laws of PN and biased PN were proposed by Erer et al [28][29][30][31][32] In addition, some new guidance strategies of impact-angle-control were also reported in literatures [33][34][35][36] in the case of without LOS angle rate information or with the limit of seeker's field-of-view.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the motivation for extending the class of allowed inverse optimal control formulations comes from the recent interests in the variants of the PNG that can enhance range observability in passive homing missiles. The observability enhancement objective typically demands a weaving-like manoeuvre pattern to induce variations in the line-of-sight rate [16][17][18]. The noticeable characteristic of the dual optimal control and estimation problem is that the design should trade off between two conflicting objectives; observability enhancement benefits from manoeuvre maximisation, whereas steering reduction benefits from manoeuvre minimisation.…”
mentioning
confidence: 99%